Pemberdayaan Usaha Kecil dan Mikro melalui Dana Zakat Produktif - Prahesti, Danica Dwi; Putri, Priyanka Permata (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2018)
The problem of poverty and socio-economic inequality is still experienced by the Indonesian people, especially in the aspect of community income. To increase the income of the community, it is necessary to change the character of the consumptive society into a productive society. Zakat funds can be utilized for productive efforts to procure capital and / or infrastructure and facilities for mustahik so that they can improve the quality of the people. This study aims to see how the role of productive zakat funds as capital in influencing the increase in SME turnover given to the mustahik assisted by Rumah Zakat in 30 cities and 48 ICD regions in 2016. This type of quantitative research uses simple linear regression method with data sources derived from from the capital and turnover data of 1672 mustahik Rumah Zakat. The results showed that UKM assistance for Zakat Houses given to poor asnaf class beneficiaries was 91.26%, and capital had a strong relationship to turnover with a large influence of capital on turnover of 44.7% where a large model of capital influence on turnover was y' = 1,285,584,312 + 1,217x. Â  Masalah kemiskinan dan ketimpangan sosial ekonomi masih dialami oleh rakyat Indonesia khususnya dalam aspek pendapatan masyarakat. Untuk meningkatkan pendapatan masyarakat perlu mengubah karakter dari masyarakat konsumtif menjadi masyarakat produktif. Dana zakat dapat didayagunakan untuk usaha produktif pengadaan modal dan/atau infrastruktur serta sarana kepada para mustahik sehingga bisa meningkatkan kualitas umat. Penelitian ini bertujuan untuk melihat bagaimana peran dana zakat produktif sebagai modal dalam mempengaruhi peningkatan omzet UKM yang diberikan kepada para mustahik binaan Rumah Zakat di 30 kota dan 48 wilayah ICD pada tahun 2016. Penelitian dengan jenis kuantitatif ini menggunakan metode regresi linear sederhana dengan sumber data berasal dari data modal dan omzet 1672 mustahik Rumah Zakat. Hasil penelitian menunjukkan bahwa bantuan UKM Rumah Zakat yang diberikan kepada penerima manfaat golongan asnaf miskin sebesar 91,26%, dan modal memiliki hubungan yang kuat terhadap omzet dengan besar pengaruh modal terhadap omzet sebesar 44,7% dimana model besar pengaruh modal terhadap omzet yaitu yâ€™ = 1.285.584,312 + 1,217x.